2008
DOI: 10.4067/s0717-95022008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplasic Ameloblastoma in Maxilla: Report of Case and Review of the Literature

Abstract: SUMMARY:The ameloblastoma is a benign neoplasm of epithelial odontogenic origin, slowly growing, locally invasive and it is the most common odontogenic tumor in the jaws. Histologically, various types have been described in literature. The desmoplastic variant is rare and characterized by difference in the typical findings of ameloblastoma, including localization, radiographic and histological features. The purpose of this article is to report a case of desmoplastic ameloblastoma in the left maxilla, and revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Frequently, the tumor is asymptomatic, the tumefaction is painless and expansion of the involved bone is the commonly observed clinical manifestations. 14 In a review of 115 cases of desmoplastic ameloblastomas, the commonly observed radiographic features were mixed radiolucent/radiopaque (56%), multilocular (49%), and with ill-defined borders (64%). 12 In the present case, multolocular radiolucency was observed in the mandibular anterior region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequently, the tumor is asymptomatic, the tumefaction is painless and expansion of the involved bone is the commonly observed clinical manifestations. 14 In a review of 115 cases of desmoplastic ameloblastomas, the commonly observed radiographic features were mixed radiolucent/radiopaque (56%), multilocular (49%), and with ill-defined borders (64%). 12 In the present case, multolocular radiolucency was observed in the mandibular anterior region.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral layer of the cells is usually cuboidal and occasionally hyperchromatic. 14 The morphologic characteristics typical of multicystic ameloblastomas such as the polarity inversion and typical palisade pattern are not observed frequently. The central portion of the tumoral islands resembling stellate reticulum is occasionally encountered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation